The Role of M1 and M2 Macrophages in Prostate Cancer in relation to Extracapsular Tumor Extension and Biochemical Recurrence after Radical Prostatectomy. (11th March 2014) - Lanciotti, M.; Masieri, L.; Raspollini, M. R.; Minervini, A.; Mari, A.; Comito, G.; Giannoni, E.; Carini, M.; Chiarugi, P.; Serni, S.
Abstract : Introduction . The aim of our work was to investigate the causal connection between M1 and M2 macrophage phenotypes occurrence and prostate cancer, their correlation with tumor extension (ECE), and biochemical recurrence (BR). Patient and Methods . Clinical and pathological data were prospectively gathered from 93 patients treated with radical prostatectomy. Correlations of commonly used variables were evaluated with uni- and multivariate analysis. The relationship between M1 and M2 occurrence and BR was also assessed with Kaplan-Meier survival analysis. Results . Above all in 63.4% there was a M2 prevalence. M1 occurred more frequently in OC disease, while M2 was more represented in ECE. At univariate analysis biopsy and pathologic GS and M2 were statistically correlated with ECE. Only pathologic GS and M2 confirmed to be correlated with ECE. According to macrophage density BCR free survival curves presented a statistically significant difference. When we stratified our population for M1 and M2, we did not find any statistical difference among curves. At univariate analysis GS, pTNM, and positive margins resulted to be significant predictors of BCR, while M1 and M2 did not achieve the statistical significance. At multivariate analysis, only GS and pathologic stage were independent predictors of BR. Conclusion . In our study patients with higher density of M count were associated with poor prognosis; M2 phenotype was significantly associated with ECE.